The Impact of COVID-19 on Admissions and In-hospital Mortality of Patients With Stroke in Korea: An Interrupted Time Series Analysis - Youngs Chang; Soo-Hee Hwang; Haibin Bai; Seowoo Park; Eunbyul Cho; Dohoung Kim; Hyejin Lee; Jin Yong Lee (Journal of Preventive Medicine and Public Health)
Objectives This study aimed to investigate the impact of coronavirus disease 2019 (COVID-19) on admission rates and in-hospital mortality among patients with ischemic and hemorrhagic stroke. Methods We constructed a dataset detailing the monthly hospitalizations and mortality rates of inpatients with stroke from January 2017 to December 2021. Employing an interrupted time series analysis, we explored the impact of COVID-19 on hospitalizations and 30-day in-hospital mortality among stroke patients. Results The number of ischemic stroke admissions decreased by 18.5%, from 5335 to 4348, immediately following the COVID-19 outbreak (p<0.001). The in-hospital mortality rate for ischemic stroke increased slightly from 3.3% to 3.4% immediately after the outbreak, although it showed a decreasing trend over time. The number of hemorrhagic stroke admissions fell by 7.5%, from 2014 to 1864, immediately following the COVID-19 outbreak. The 30-day in-hospital mortality rate for hemorrhagic stroke initially decreased from 12.9% to 12.7%, but subsequently showed an increasing trend. Conclusions We confirmed that COVID-19 impacted both the admission and death rates of stroke patients. The admission rate for both ischemic and hemorrhagic strokes decreased, while in-hospital mortality increased. Specifically, in-hospital mortality from ischemic stroke rose initially after the outbreak before stabilizing. Additionally, our findings indicate variable effects based on sex, age, and socioeconomic status, suggesting that certain groups may be more susceptible. This underscores the need to identify and support vulnerable populations to mitigate adverse health outcomes.